Pemikiran Ibnu Asyur Terhadap Modernisasi Hukum Islam - Surono, Yudi; Nurjanah, Siti; Zulaikha, Siti; Hermanto, Agus (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The article discusses the thoughts of Muhammad Thahir Ibn Asyur, a Tunisian Muslim scholar known for his contributions in the fields of ushul fiqh and tafsir, especially in developing the concept of maqashid al-syari'ah. Ibn Asyur emphasized the importance of understanding Islamic law not only from a textual perspective, but also from the goals and values that the sharia seeks to achieve. He offers a contextual approach to ijtihad through maqashid sharia to answer the challenges of the modern era, without ignoring the basic principles of Islam. The concept of maqashid that he put forward not only covers the five main goals of sharia—namely protection of religion, soul, mind, descendants, and property—but is also expanded to include values such as justice, freedom, and public welfare. This article shows that Ibn Asyur's approach is solution-oriented and progressive, bridging traditional thinking and contemporary needs. His ideas became an important foundation in the modernization of Islamic law which remains based on the essential values of religion, while being relevant to the development of modern society.